Marketplace Application Analysis And Design Of Paid Software And Web-Based Shareware Services - Yonatan Widianto; Robby Kurniawan Budhi; Kevin Cornelius (JOINCS (Journal of Informatics, Network, and Computer Science), 2022)
In this digital era, many people do shopping online. The ease of application facilities offered is a consideration for people doing business transactions, especially during the Covid-19 period. Along with these changing trends, many business actors are also implementing their marketing strategies through various media such as social media, e-commerce, or marketplaces in order to continue to contribute to business income. This electronic marketing strategy makes it possible to market targeted offerings and in turn, build stronger customer loyalty. Like the Marketplace, paid software and shareware products have specific features. This study aims to analyze and design a marketplace application for paid software services and shareware. Applications are developed using the Waterfall method, through analysis, design, coding, testing, and system maintenance. The analysis and design use standard object-oriented tools with the Unified Modeling Language (UML) model. Model Document diagram contains Use case Diagrams, Class Diagrams, and Sequence Diagrams. The results of this study are in the form of an overview of needs analysis and application design as a reference in making applications for transactions in the marketplace.